Minimizing the Effects of Multi-rate WLANs by Adapting Link Adaptation and Call Admission Interfaces - Tueysuez, M. Fatih; Mantar, Haci A. (Springer-Verlag Berlin, 2010)
Link Adaptation (LA) is a term used in wireless communications to adjust the physical transmission rate of nodes according to the channel conditions it senses and optimize the bit transmission by using multi-rate transmissions. It has a direct impact on the transmissions of all active calls and can cause a general degradation on the quality of service (QoS). Besides, Call admission control (CAC) is used in the call set-up phase and it determines whether it has sufficient resources to accept a new call. However, CAC also does not work efficiently on the existence of transmission rate changes. Since IEEE 802.11 standard was not created for voice communications in first place, it brings a lot of new limitations for successfully deploying VoIP. In this paper, we propose a fast and efficient, algorithm which integrates LA interface, codec-frame size adaptation and CAC interface to minimize the impact of multi-rate transmission and optimize the maximum throughput and voice quality over multi-rate WLANs.
2nd International Conference on Networked Digital Technologies -- JUL 07-09, 2010 -- Charles Univ, Prague, CZECH REPUBLIC
Keywords: Voice over IP; Link adaptation; Call admission control; multi-rate WLANs; QoS; IEEE 802.11e